TRAINING IN THE MAKING OF DISHWASHER SOAP FOR GROWING THE ENTREPRENEURSHIP SPIRIT OF STUDENTS AT SMA NEGERI 4 PEMATANG SIANTAR - Hendri Mayanta Tarigan; Josep Lubis; Maswan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
A very good business opportunity for students of SMA Negeri 4 Pematang Siantar because the location of the school is very strategic with residential communities. Adjacent to community settlements is a very good opportunity for them. Through community service carried out by the Efarina Siantar University Community Service Team, it helps them and motivates them to develop their entrepreneurial spirit. Students wish to increase their pocket money and create jobs for the local community. After this community service activity, partners need support and assistance regarding legal aspects and aspects of making liquid dish soap.